Structural characterization, magnetic studies, and catecholase-like activities of Mn12 clusters. Issue 14 (18th July 2018) - Ashafaq, Mo; Raizada, Mukul; Khalid, Mohd; Shahid, M.; Ahmad, Musheer; Siddiqi, Zafar A.
Abstract: Two polynuclear, mixed-valence, sandwich dodecanuclear manganese clusters [Mn II 4 Mn III 4 Mn II 4 (μ4 -O)2 (μ3 -O2 CH)2 (thme)4 (MeCO2 )10 (H2 O)4 ]·4H2 O (1 ) and [Mn II 4 Mn III 4 Mn II 4 (μ4 -O)2 (μ3 -O)2 (thmp)4 (MeCO2 )10 (H2 O)4 ]·10H2 O (2 ) are reported by the reaction of 1, 1, 1-tris(hydroxymethyl)ethane (H3 thme) or 1, 1, 1-tris(hydroxymethyl)propane (H3 thmp) with manganese(II) salts in methanol under reflux conditions.1 and2 were characterized by single-crystal X-ray diffraction, PXRD, cyclic voltammetry (CV), and variable temperature magnetic studies.1 and2 crystallize in the monoclinic (P21 /n) and triclinic (P-1) systems, respectively, and each structure consists of a dodecanuclear mixed-valent sandwich core. Magnetic data confirmed that both complexes show dominant antiferromagnetic interactions between metal centers. The fascinating features of the non-covalent supramolecular contacts have been explored. The interplay of O⋯H interactions ( i.e. O–H⋯O and C–H⋯O contacts) gives rise to the consolidation of discrete units of1 and2 into supramolecular architecture. Catecholase activity data show that the present clusters catalyze the oxidation of 3, 5-DTBC to 3, 5-DTBQ with efficient K cat values. Abstract :